Respuesta :
Answer : The solution to the system of equations is, (6, -8)
Step-by-step explanation :
As we are given the two equations:
[tex]y=\frac{1}{3}x-10[/tex] ............(1)
[tex]2x+y=4[/tex] ..........(2)
Now put equation 1 in equation 2, we get:
[tex]2x+y=4[/tex]
[tex]2x+(\frac{1}{3}x-10)=4[/tex]
[tex]2x+\frac{1}{3}x-10=4[/tex]
[tex]\frac{7}{3}x-10=4[/tex]
[tex]\frac{7}{3}x=4+10[/tex]
[tex]\frac{7}{3}x=14[/tex]
[tex]x=14\times \frac{3}{7}[/tex]
[tex]x=6[/tex]
Now put the value of 'x' in equation 1, we get:
[tex]y=\frac{1}{3}x-10[/tex]
[tex]y=(\frac{1}{3}\times 6)-10[/tex]
[tex]y=2-10[/tex]
[tex]y=-8[/tex]
Thus, the solution to the system of equations is, (6, -8)